THE ROLE OF MALAY GAMBUS MUSIC IN EDUCATION AND CULTURAL PRESERVATION: A CASE STUDY - Fitriah, Laila; Jazuli, Muhammad; Wadiyo, Wadiyo; Sugiarto, Eko (JURNAL EDUSCIENCE, 2025)
Purpose:This study aimed to explore the role of Gambus Melayu music as an educational medium for preserving local culture at the Cendana Rumbai Education Foundation High School. Instilling local cultural values in formal education is a strategic way to maintain the nation's cultural identity in the era of globalization.Methodology:A  qualitative descriptive research design was employed with a case study method. Data were collected through classroom observations, interviews, and documentation. The writer also observes the extracurricular activities related to Gambus Melayu music. This method is conducted to understand how traditional music functions in formal education.Findings:Research results indicated that Gambus music has various functions, including as a teaching material for arts education, instilling local wisdom values, fostering Malay cultural identity, and appreciating local wisdom. Furthermore, incorporating gamelan music into the curriculum provides students with an understanding of local culture. It even provides an extraordinary and meaningful learning experience aligned with current learning principles.Contribution:This study empirically enhances cultural education by integrating traditional music into formal education at SMA Cendana. This school serves as an effective technique to preserve local cultural continuity in the modernisation era. It gives teachers and stakeholders helpful ideas for how to use school-based programs to help protect culture.